How Should Impacts Be Assessed? - Rosqvist, Gunhild; Heikkinen, Hannu I.; Suopajärvi, Leena; Österlin, Carl (Cambridge University Press, 2022)
Industrial development and resource exploitation in Arctic Fennoscandia have caused cascading and cumulative effects on environment and people since the late nineteenth century. The increasing demand for minerals and metals to facilitate a ‘green transition’ now pose further challenges for environmental and social management. In this chapter we present local attempts to provide additional knowledge and understanding of the full impact from multiple human activities beyond conventional corporate-led impact assessments. With the aim to reveal the full range of impacts from industrial developments on their livelihood, Laevas, Gabna and Semisjaur-Njarg Sámi reindeer herding communities in Sweden produced their own assessment of cumulative effects based on detailed analysis of their land use needs. The municipal level is an important local land use planning forum. Our case examples from Sodankylä municipality in Finland exemplify how challenging it may be to fully understand and manage cumulative impacts from new industrial projects. We note that effects of climate change are not yet incorporated in any assessments of impacts in any satisfactory manner.